KAJIAN LOKASI TEMPAT TINGGAL PNS PEMERINTAH KABUPATEN MAGELANG - , Farida Nurul Aini ([Yogyakarta] : Universitas Gadjah Mada, 2014)
One factor in choosing residential location is the distance to the workplace. Theoretically, there should be a lot of housing developed around the government offices. However, in Kota Mungkid and surrounding areas, there is not so many residential-housing that have been developed. The purpose of this study was to identify factors that affect in the selection of residence location and the relationship between the choice of where to live with respondent characteristics. This research is deductive descriptive wit (proportional random sampling. The population in this study were all Magelang District Government employees who work in Kota Mungkid, which amounts to 1,814 people. Due to limited time and funds, then the sample is 60 people. The assumptions used to determine the proportion of the samples/respondents is the distance from residence to work place. Close proximity to the workplace is assumed that the empolyees residing within a radius of 10 km, while far is beyond a radius of 10 km. The results showed that there are three factors that affect the civil government of Magelang Regency in the choice of location of residence, such as social, economic factors, and physical factors. However, these three factors have a different effect on each respondent. Respondents reside away with work due to an adequate road network is also supported by private vehicle ownership mode of transportation to and from work. There is a relationship between the preferred place to stay that is close to the workplacewith the characteristics of the respondents, namely age and years of service. Respondents with a service life of over 20 years, many are choosing to live closer to work because of the housing facilities provided by the government at the beginning of his tenure. While respondents with tenure of less than 10 years, choosing a place to stay close to their work because they are mostly new family, who newly build the economy of the family together.